El Ballet Folkl?rico de Cal Poly, 1994 - Juan Martinez::::::photographer::: (1994)
Back of print reads: 'Front to Back [new line] Esmeralda Vasquez 2nd Biochem [new line] Rosalba Sahagun 3rd Human Develo [new line] Esther Ramos 2nd Archet [new line] Carmen Barragan ARCE Senior [new line] Region Sinaloa [new line] El Ballet Folkl?rico de Cal Poly [at bottom] Mustang Daily Files 1994 [in large letters] Juan'. Mott Gym is visible in the background.